2007
DOI: 10.1007/s00381-007-0429-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled analgesia with fentanil and midazolam in children with postoperative neurosurgical pain

Abstract: PCA with fentanil plus continuous infusion of midazolam is a safe and efficacious method for analgesia in children with moderate to severe postoperative neurosurgical pain. The association of midazolam to fentanil also contributes to control anxiety and stress in this subset of patients and does not show any important side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
1
6
0
4
Order By: Relevance
“…Stewart et al reported that the mixed infusion of ondansetron with midazolam and fentanyl was stable for 24 hours [9]. In a study by Chiaretti et al [10], an effective result was achieved without any particular problems when fentanyl and midazolam were mixed and infused into PCA patients. Thus, the authors considered the mixed solution of fentanyl, ondansetron, and midazolam to be safe and physicochemically stable.…”
Section: Methodsmentioning
confidence: 99%
“…Stewart et al reported that the mixed infusion of ondansetron with midazolam and fentanyl was stable for 24 hours [9]. In a study by Chiaretti et al [10], an effective result was achieved without any particular problems when fentanyl and midazolam were mixed and infused into PCA patients. Thus, the authors considered the mixed solution of fentanyl, ondansetron, and midazolam to be safe and physicochemically stable.…”
Section: Methodsmentioning
confidence: 99%
“…Fentanyl PCA has been used safely and effectively following neurosurgery (Chiaretti et al, 2008 Level IV), thoracic surgery (Butkovic et al, 2007 Level III-1) and tonsillectomy (Antila et al, 2006 Level II), and for acute cancer-related pain (Ruggiero et al, 2007 Level IV). In comparison with morphine, tramadol PCA provided minor improvements in time to extubation post cardiac surgery Level II) and reduced nausea post-tonsillectomy but at the cost of higher pain scores (Ozalevli et al, 2005 Level II).…”
Section: The Pca Prescriptionmentioning
confidence: 99%
“…Çalışmamızda postoperatif analjezide optimal ağrı kontrolü, yüksek hasta-aile mennuniyeti ile beraber güvenli ve efektif bir ağrı yönetimi sağlayan PCA yöntemini tercih ettik (17)(18)(19)(20)(21). PCA da hastanın kendi denetimindeki bolus dozlar sayesinde ağrı kesici ihtiyacı duyduğu zamanla ağrı Şekil1.…”
Section: Discussionunclassified
“…PCA da hastanın kendi denetimindeki bolus dozlar sayesinde ağrı kesici ihtiyacı duyduğu zamanla ağrı Şekil1. Grup 1 ve 2 VAS grafiği kesici uygulanması arasında bekleme süresi olmaması avantajını kullandık (18). Biz bu çalışmada ise postoperatif ağrı değerlendirmesinde sözel iletişim kurabilen ve kavramları gelişen yedi yaş üzeri çocuklarda 0-10 cm arasında VAS skorlaması uyguladık.…”
Section: Discussionunclassified